From the Clinic to the Laboratory, and Back Again: Investigations on Cannabinoids and Endocannabinoid System Modulators for Treating Schizophrenia - Hoffman, Kurt Leroy (Frontiers in Psychiatry, 2021)
The present mini-review focuses on animal models of schizophrenia that have explored the effects of cannabidiol (CBD; a non-psychoactive component of cannabis) or the pharmacological manipulation of the endocannabinoid system on behavioral and cognitive outcome measures. First, results of some relevant clinical studies in this area are summarized, and then pre-clinical work on animal models of schizophrenia based on NMDA receptor antagonism or neurodevelopmental manipulations are discussed. A brief overview is given of the theoretical framework on which these models are based, along with a concise summary of results that have been obtained. Clinical results using CBD for schizophrenia seem promising and its effects in animal models of schizophrenia support its potential as a useful pharmacotherapy. Animal models have been paramount for elucidating the actions of CBD and the function of the endocannabinoid system and for identifying novel pharmacological targets, such as cannabinoid receptors and anandamide. However, more attention needs to be placed on defining and applying independent variables and outcome measures that are comparable between pre-clinical and clinical studies. The objective of this review is, on the one hand, to emphasize the potential of such models to predict clinical response to experimental drugs, and on the other hand, to highlight areas in which research on such models could be improved.